A headway and order scheme based mixed integer goal programming model for railway rescheduling / Zuraida Alwadood - Alwadood, Zuraida (Institute of Graduate Studies, UiTM, 2018)
Service disruptions in rail transport services often lead to trains cancelations and delays. The disruptions can create conflicts in the use of tracks and platforms and further propagate the disruptions throughout the railway system. The challenge in rescheduling trains is to quickly find the solution to the problem by synchronising resources to minimise the effect of the disruption. Railway rescheduling involves real-time alteration of train schedules in a railway network which is highly interconnected. Mathematical modeling for trains rescheduling has always been considered as a difficult and heavily constrained combinatorial optimisation problem that involves a large number of hard (operational) constraints and soft (desirability) constraints and the complexity of problem increases with the number of decision variables and constraints. Modelling and solving railway rescheduling problem is thus considered a highly complex task and categorised as an NP-hard class problem. This study is concerned with solving the railway rescheduling problem when disruption occurs on a track segment of the railway. Among the objectives of the study are to analyse the causes of railway disruptions and delay problems and to develop the visual railway network topology for the local Komuter rail system. The main contribution of the study is the formulation of a Mixed Integer Goal Programming (MIGP) model that determines a rescheduled timetable, generated based on trains priority rules, which are outlined according to the types of trains. The model aims at achieving two goals, where the first objective function is to minimise the total delay time of all trains in the network, while the second objective function is to maximise the train service reliability…